Validation of a clinical trial composite endpoint for patients with necrotizing soft tissue infections. Issue 4 (October 2017) - Bulger, Eileen M.; May, Addison; Dankner, Wayne; Maislin, Gregory; Robinson, Bryce; Shirvan, Anat
Abstract : OBJECTIVE: Our objective was to develop and validate a composite endpoint for patients with necrotizing soft tissue infections that incorporates: local tissue injury, systemic organ dysfunction, and mortality. METHODS: The Necrotizing Infection Clinical Composite Endpoint (NICCE) was defined as follows:(i) alive at day 28, (ii) three or less debridements before day 14, (iii) no amputation beyond first debridement, (iv) modified sequential organ failure assessment score score (mSOFA) at day 14 ⩽ 1. To be considered a success, all individual criteria must be met. Several data sets were used to assess validity: (i) a retrospective data set of 198 patients treated during 2013 at 12 US trauma centers; (ii) a subset with high disease acuity, admission mSOFA score of 3 or higher (n = 69); and (iii) 40 patients from a multicenter, phase 2 randomized trial of a CD28 immunomodulator (AB103). Clinical success based on each parameter and the composite score was assessed. RESULTS: Using the retrospective data set for all patients and those with high disease severity (respectively), survival rates were 92% and 84%; day 14 mSOFA 1 or lower score was 69% and 51%; three or less debridements was 84% and 77%; and no subsequent amputations were 96% and 94%. Overall, the percent meeting all success criteria for NICCE was 58% (all patients) and 33% (mSOFA > 3). NICCE success was also associated with reduced utilization of health care resources, intensive care unit–free days were median (interquartile range) of 25.3 (21.9–28) and 19.6 (4.3–25.1) days (one-sided Wilcoxon p < 0.001) and ventilator-free days were 28 (26–28) versus 25 (14–28) ( p < 0.001) for NICCE success versus failure, respectively. Using the phase 2 data set, the treated group (0.5 mg/kg, n = 15) demonstrated a NICCE success rate of 73.3% versus 40% for placebo (n = 10). CONCLUSION: These data demonstrate internal consistency of the components and face and criterion validity of the NICCE endpoint. NICCE offers an opportunity to demonstrate a clinically relevant treatment effect for patients enrolled in clinical trials for necrotizing soft tissue infection. Level of Evidence: Prognostic/Epidemiological, level III; Therapeutic, level IV.